The first zoeal stage of the genus Cronius (Brachyura, Portunidae) from the Brazilian coast, hatched in a laboratory - Fransozo, A.; Mantelatto, F. L.; Bertini, G. (Oxford University Press, 2002)
This study describes the first zoeal stage of Cronius ruber and Cronius tumidulus. The zoeae can be distinguished using the setation of the cephalic appendages and the lateral process on the abdominal somite.